The collaborative dialogue and the collaborative tasks assisting the learning of English - Führ, Mirian (BELT - Brazilian English Language Teaching Journal, 2011)
This paper presents the collaborative dialogue as a possible learning mediator of English as a foreign language and discusses how this kind of dialogue promotes interaction among students and, consequently, influences in the learning of the target language. In order to do this, it looks for theoretical bases in the sociocultural theory and, mainly, in Swain (2000), Swain and Lapkin (2001), Lima (2006), Lima and Pinho (2007), among others. The data obtained with the realization of a collaborative task with four English learners at a pre-intermediate level of proficiency in a language course were analyzed. The data analysis made evident the positive influence of the collaborative dialogue to the learning of English and revealed the necessity of using collaborative tasks in the teaching of languages at schools as a means of developing the learners’ four language skills.